Approximate, numerical and experimental investigations of a water hammer in Vrhovo bulb-turbines hydropower plant - Bergant, Anton; Perkolj, Jošt (Journal of Energy Technology, 2026)
This paper investigates effectiveness and accuracy of approximate and numerical water hammer models in the Sava River bulb turbine hydropower plants. The approximate and numerical rigid water hammer models are introduced first. The computational results are compared with the results of measurements in Vrhovo hydropower plant. Comparisons of the computed and measured results are examined for emergency shutdown case. The water hammer is controlled by appropriate adjustment of the guide vane and runner blade closing/opening laws. There is a good agreement between the approximate and numerical, and measured results.